Food Innovation in the Frame of Circular Economy by Designing Ultra-Processed Foods Optimized for Sustainable Nutrition - Capozzi, Francesco (Frontiers in Nutrition, 2022)
Despite the large debate about the relationship between the ultra-processed foods and the prevalence of some diet-related diseases, the innovative potential of various processing technologies has been evidenced in pathways that could lead to modifications of the food matrix with beneficial health effects. Many efforts have been directed towards the conjugation of a healthy diets and a sustainable exploitation of natural resources for the preparation of accessible foods. This minireview highlight the possible links between processing, sustainability and circular economy through the valorisation of by-products that could be exploited to prepare nutrients-rich ingredients at lower economic and environmental costs. The assessment of the quality and safety of functional foods based on ingredients derived from food-waste requires a more robust validation by means of the food-omics approach, that consider not only the composition of the final products but also the structural characterization of the matrix, as the bioaccessibility and the bioavailability of nutrients are strictly dependent on the functional characteristics of the innovative ingredients.